Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2): a review - Wei Feng; Wei Zong; Feng Wang; Shaoqing Ju (Molecular Cancer, 2020)
Abstract In recent years, the prevalence and spread of coronavirus has had a huge impact on global public health. Due to the incomplete understanding of the pathogenic mechanism of the virus, it is difficult for humans to fight against the virus quickly and effectively once the outbreak occurs. In early 2020, a novel coronavirus was discovered in Wuhan, China. Soon after, similar cases were found in other countries around the world, and the number of infected people increased rapidly. So far, the global cumulative number of infected people has exceeded 3 million, and more than 200,000 people have died, which has had a huge impact on global human health and economic development. Every outbreak of disease makes a deep impression on mankind. Herein, we summarize the virology, epidemiology, clinical manifestations, diagnosis, treatment and prevention of SARS-CoV-2, and hope that countries can control the outbreak as soon as possible to minimize the loss.